Panic Attacks in Patients with Supraventricular Tachycardia: Problems of Differential Diagnosis and Impact on Quality of Life - D. A. Tsaregorodtsev; P. A. Shelukha; L. V. Romasenko; M. M. Beraya; A. V. Sokolov (Рациональная фармакотерапия в кардиологии, 2022)
Aim. To study the psychosomatic relationships and quality of life (QOL) of patients with paroxysmal supraventricular tachycardia (SVT) depending on the presence or absence of panic attacks (PA) in comparison with patients with heartbeat against the background of somatoform autonomic dysfunction.Material and methods. The study included patients with SVT and heart attacks due to sinus tachycardia in the context of somatoform autonomic disorder (SAD). All patients were interviewed to identify anxiety and depressive disorders (Hospital Anxiety and Depression Scale [HADS] and Hamilton's Depression Scale), QOL assessment (SF-36 questionnaire), and they were also consulted by a psychiatrist who established the presence or absence of PA. According to a visual analogue scale, in points from 0 to 6, we assessed the general state of our patients' health (0 points corresponded to complete health, and 6 points corresponded to a serious illness) and the effect of heartbeat on well-being (0 points - no arrhythmia, 6 points - arrhythmia «nterferes with life»).Results. The study included 96 patients: 60 with SVT (21 men, 39 women, average age was 51 [33; 61] years) and 36 with heart attacks caused by sinus tachycardia in the framework of somatoform autonomic disorder (10 men, 26 women, average age was 33 [27; 41] years). Panic disorder was diagnosed in the SVT group in 17 patients, accounting for 28.3%. Only 7 patients (41%) could clearly differentiate between SVT and PA attacks. The low sensitivity of the HADS questionnaire in patients with SVT determined the need to consult a psychiatrist for the diagnosis of panic disorders.Conclusion. PA is typical for 28.3% of patients with SVT. The combination of SVT with PA reduces the QOL of patients due to its mental components, including due to the more frequent occurrence of depressive symptoms. Patients with SAD subjectively perceive the heartbeat as a more significant factor affecting health, compared with patients with SVT. Difficulties in the differential diagnosis of PA and SVT paroxysms in real clinical practice often lead to the appointment of the same therapy without taking into account the differences in the genesis of heartbeats.